2002
DOI: 10.1103/physrevlett.89.085002
|View full text |Cite
|
Sign up to set email alerts
|

MeV Ion Jets from Short-Pulse-Laser Interaction with Thin Foils

Abstract: Collimated jets of carbon and fluorine ions up to 5 MeV/nucleon ( approximately 100 MeV) are observed from the rear surface of thin foils irradiated with laser intensities of up to 5 x 10 (19)W/cm(2). The normally dominant proton acceleration could be surpressed by removing the hydrocarbon contaminants by resistive heating. This inhibits screening effects and permits effective energy transfer and acceleration of other ion species. The acceleration dynamics and the spatiotemporal distributions of the accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
181
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(189 citation statements)
references
References 24 publications
5
181
2
1
Order By: Relevance
“…Because of the presence of hydrocarbon and water vapour on the surfaces of the foils (for experiments performed at typical vacuums of approximately 10 K5 mbar), protons are usually observed in large numbers, and due to their high charge-to-mass ratio they are more efficiently accelerated than heavier ion species and effectively screen the electric acceleration fields experienced by heavier ions. Recent studies have shown that in order to efficiently accelerate heavier ions the proton source layers should be removed from the target foil by heating or ablation (Hegelich et al 2002;McKenna et al 2004). In addition to ion acceleration in the forward direction (direction of laser propagation), we note that plasma expansion at the front surface of the target foil can also lead to ion acceleration in the backward direction.…”
Section: Ion Acceleration Mechanismsmentioning
confidence: 99%
“…Because of the presence of hydrocarbon and water vapour on the surfaces of the foils (for experiments performed at typical vacuums of approximately 10 K5 mbar), protons are usually observed in large numbers, and due to their high charge-to-mass ratio they are more efficiently accelerated than heavier ion species and effectively screen the electric acceleration fields experienced by heavier ions. Recent studies have shown that in order to efficiently accelerate heavier ions the proton source layers should be removed from the target foil by heating or ablation (Hegelich et al 2002;McKenna et al 2004). In addition to ion acceleration in the forward direction (direction of laser propagation), we note that plasma expansion at the front surface of the target foil can also lead to ion acceleration in the backward direction.…”
Section: Ion Acceleration Mechanismsmentioning
confidence: 99%
“…Through the TNSA mechanism a beam of protons (but also photons and electrons) with the typical broad spectrum shown in figure 1 was produced. The acceleration of heavy ions via TNSA from TARANIS or any other laser with similar characteristics is very inefficient [6]. The accelerated particles were made to pass through a collimator and a magnet.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand experiments where the target is pre-heated and thus the contamination layers are removed show a reduced proton signal whereas the ion signal is enhanced [14,76]. A pre-heated target, coated with CaF 2 at the rear side only was used to identify the "rear-side" acceleration to be responsible for the ion acceleration [76]. Once more it seems that neither the "front-side" nor the "rear-side" can explain all observed phenomena at once.…”
Section: Alternative Acceleration Mechanismsmentioning
confidence: 99%
“…But also this feature is discussed controversy since a saturation of the used CR39-detector can explain this structure [75]. On the other hand experiments where the target is pre-heated and thus the contamination layers are removed show a reduced proton signal whereas the ion signal is enhanced [14,76]. A pre-heated target, coated with CaF 2 at the rear side only was used to identify the "rear-side" acceleration to be responsible for the ion acceleration [76].…”
Section: Alternative Acceleration Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation